Absence of association between the allele coding methionine at position 29 in the N-terminal domain of ICAM-1 (ICAM-1Kilifi) and severe malaria in the northwest of Thailand - Jun Ohashi (2018)
Intercellular adhesion molecule 1 (ICAM-1) is known to be the endothelial receptor for Plasmodium falciparum-infected erythrocytes. Associations of the variant allele coding methionine at position 29 in the N-terminal domain of ICAM-1, ICAM-1Kilifi, with severe malaria have been investigated in African populations, and the results of these investigations have varied widely. In this study, we investigated a possible association between the ICAM-1Kilifi and severe malaria in adult malaria patients living in northwest Thailand. The frequencies of the ICAM-1Kilifi among patients with mild malaria, with non-cerebral severe malaria, and with cerebral malaria were 1.7%, 2.7%, and 2.3%, respectively. This variant showed neither positive nor negative association with severe malaria in Thailand.